A study of origins and growth of Sufi movement - Sharmila (Innovative Research Thoughts, 2017)
Mysticism in Islam is known as Sufism or Tasawwuf. The word Sufism refers to the encompassing philosophy and practices that seek to establish a direct relationship between God and man, and people who follow this path are known as Sufis. Although the term Sufi is not found in the Qur'an or the books of Hadith and does not appear in the standard Arab dictionaries until the 8th century author of al Risala coined it, it was not in common use until the beginning of the 9th century, when it was used as a generic term to describe individuals adopting a particular religious attitude based on austerity and spirituality. After the death of the Prophet Muhammad (S.A.W. ), the sole title offered to Muslims was Sahabi (companion), as he explains simply: "After the Prophet Muhammad (S.A.W. The followers of Sufism or Tasawwuf believe that their religion was first taught by Muhammad. They think the Prophet got revelations in two ways: via the words of the and by the divine inspiration in his heart. The former was intended for everyone, while the latter was supposed to be shared only among a select group of people and passed on "from heart to heart." Knowledge of the words of the Qur'an and hadith was referred to as ilm-e-safina, while ilm-e-sina referred to "knowledge of the heart." Most historians agree that the origins of Sufism may be traced back to the late 2nd or early 3rd century of the Islamic period. Certain contemporary academics have made the unfortunate association between Sufism and Greek Philosophy.